(untitled) (Ciudades, 2017)
The article presents the formation, the actual problems and the rehabilitation policies of the socialist housing estates built between the fifties and the eighties in Hungary. We intend to give an overview over the evolution of the social housing model after World War II in this region of Central Europe and its changes in the following decades. After the political and economical changes of 1990, practically from the 2000s rehabilitation processes of these quarters appear. The study examines the two main policies of urban regeneration of housing estates: governmental programmes that principally aim the energy efficient renovation of the buildings, and integrated urban rehabilitations with European subsidies of the last few years.